News of the world [compact disc, unabridged] : a novel - Jiles, Paulette, 1943- (Brilliance Audio, 2016)
In the aftermath of the Civil War, an aging itinerant news reader agrees to transport a young captive of the Kiowa back to her people in this exquisitely rendered, morally complex, multilayered novel of historical fiction.